Educational Achievement of Second Generation Immigrants: An International Comparison - Christian Dustmann; Tommaso Frattini; Gianandrea Lanzara (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2011)
This paper investigates the educational achievements of second generation immigrants in several OECD countries in a comparative perspective. We first show that the educational achievement (measured as test scores in PISA achievement tests) of children of immigrants is quite heterogeneous across countries, and strongly related to achievements of the parent generation. The disadvantage considerably reduces, and even disappears for some countries, once we condition on parental background characteristics. Second, we provide novel analysis of cross-country comparisons of test scores of children from the same country of origin, and compare (conditional) achievement scores in home and host countries. The focus is on Turkish immigrants, whom we observe in several destination countries. We investigate both mathematics and reading test scores, and show that the results vary according to the type of skills tested. For mathematics, in most countries and even if the test scores achievement of the children of Turkish immigrants is lower than that of their native peers, it is still higher than that of children of their cohort in the home country - conditional and unconditional on parental background characteristics. The analysis suggests that higher school quality relative to that in the home country is important to explain immigrant children's educational advantage.
Keywords: 330